Designing and developing a prescription digital therapeutic for at-home heart rate variability biofeedback to support and enhance patient outcomes in post-traumatic stress disorder treatment - Macy, Rebecca; Somanji, Flavio; Sverdlov, Oleksandr (Frontiers in Digital Health, 2025)
Post-traumatic stress disorder (PTSD) is a psychiatric condition producing considerable distress, dysfunction, and impairment in affected individuals. While various forms of psychotherapy are commonly utilized in PTSD treatment, the known neurological pathologies associated with PTSD are insufficiently addressed by these conventional approaches. Heart rate variability biofeedback (HRV-BFB) is a promising tool for correcting autonomic dysfunction in PTSD, with subsequent changes in clinically significant outcome measures. This paper outlines a systematic approach for the development, distribution, and implementation of a prescription at-home HRV-BFB digital therapeutic. We provide recommendations for evidence-generation strategies and propose appropriate regulatory pathways within existing frameworks. Widespread access to HRV-BFB could potentially reduce the distress, disability, and healthcare burden associated with PTSD. Promoting HRV-BFB as a primary intervention could also serve to reduce the stigma associated with “mental” illness and increase health literacy regarding the neuroimmune impacts of psychosocial factors. These processes might in turn improve treatment-seeking, adherence, and supported self-management of these conditions.